Young status consumers pursuit of luxury brands: awareness, purchase, dream value and avoidance - Phau, Ian (Global Business and Technology Association, 2009)
The study aims to examine the impact of status consumption towards the awareness, purchase, dream value and avoidance of luxury brands. A self-administered questionnaire was generated and administered to a non-probability convenience sample of 389 young consumers. The findings suggest that status consumption is not a strong factor to influence consumer awareness, purchase, dream value and avoidance towards luxury brands. However, the research showed a positive relationship between awareness, purchase and dream value of luxury brands. This suggests each of these factors is closely associated with each other to establish consumer reaction to luxury brands. These findings broaden our understanding on the potential effects of status consumption and consumers‘ knowledge towards luxury brands.